Distinct Biological Potential of Streptococcus gordonii and Streptococcus sanguinis Revealed by Comparative Genome Analysis - Zheng, W.; Tan, M.F.; Old, L.A.; Paterson, I.C.; Jakubovics, N.S.; Choo, S.W. (Nature Publishing Group, 2017)
Streptococcus gordonii and Streptococcus sanguinis are pioneer colonizers of dental plaque and important agents of bacterial infective endocarditis (IE). To gain a greater understanding of these two closely related species, we performed comparative analyses on 14 new S. gordonii and 5 S. sanguinis strains using various bioinformatics approaches. We revealed S. gordonii and S. sanguinis harbor open pan-genomes and share generally high sequence homology and number of core genes including virulence genes. However, we observed subtle differences in genomic islands and prophages between the species. Comparative pathogenomics analysis identified S. sanguinis strains have genes encoding IgA proteases, mitogenic factor deoxyribonucleases, nickel/cobalt uptake and cobalamin biosynthesis. On the contrary, genomic islands of S. gordonii strains contain additional copies of comCDE quorum-sensing system components involved in genetic competence. Two distinct polysaccharide locus architectures were identified, one of which was exclusively present in S. gordonii strains. The first evidence of genes encoding the CylA and CylB system by the α-haemolytic S. gordonii is presented. This study provides new insights into the genetic distinctions between S. gordonii and S. sanguinis, which yields understanding of tooth surfaces colonization and contributions to dental plaque formation, as well as their potential roles in the pathogenesis of IE.